Survey on Low Back Pain among Cyclists: Prevalence, Risk Factors and Knowledge of Injury Prevention Strategies - Purushothaman, Vinosh Kumar; Chen, Wei Vvy; Subramaniam, Ambusam; Subbarayalu, Arun Vijay; Maruthey, Nithiyah; Kandasamy, Mohanraj (Physical Education Theory and Methodology, 2023)
The study aimed to determine prevalence of low back pain (LBP), risk factors, and knowledge of injury prevention strategies in recreational cyclists. Materials and methods. This cross-sectional quantitative study included 141 adult recreational cyclists aged 18 to 70. LBP prevalence was determined using a standard Nordic questionnaire. In addition, a validated self-developed questionnaire was used to assess knowledge level, with a high score representing the highest level of knowledge. Frequencies and percentages were used to report the descriptive variables, whereas the Chi-square test was used to determine the association between risk factors and LBP. Results. The study identified that 55.3% of cyclists had a lifetime prevalence of LBP, and 35.5% reported LBP in the past 12 months. However, no significant association (p>0.05) was found between the risk factor and the LBP. Despite this, a low level of knowledge of injury prevention strategies for recreational cyclists was found. Conclusions. This survey found that recreational cyclists have a low level of understanding about crucial bicycle characteristics such as seat height, saddle tilt, and handlebar position to maintain optimal body biomechanics. Recreational cyclists should be educated on the need for appropriate bicycle modifications and ergonomics, effective warm-up, stretching, and cool-down techniques, and some critical injury prevention strategies, especially in the low back.